Not just another internal service provider: how a firm's marketing research function influences uses of market research information. (25th September 2020) - Bode, Christian; Geiger, Ingmar
Abstract : Purpose: This paper aims to better understand a firm's market research function's (MRF) roles and influences on the different uses of market research information (MRI) (instrumental, conceptual and symbolic) in the firm. Design/methodology/approach: This study uses a mixed-methods design: In a qualitative study among marketing managers ( n = 9) and market researchers ( n = 10); different roles of a firm's MRF are scrutinized. The quantitative study among corporate users of MRI ( n = 235) tests a conceptual model on the MRF-related determinants of MRI uses, using structural equation modeling. Findings: When the MRF exhibits methodological, market and business expertise and interacts with market research users, these features indirectly influence instrumental, conceptual, and symbolic uses, through MRI quality perceived by the users. The users' knowledge of market research methods, the function's integrity, top management support, and decentralized decision-making have various beneficial influences on the three uses of MRI. Research limitations/implications: Broadly speaking, this research expands the theoretical understanding of marketing-related organizational learning processes. It considers message, source, recipient, and context variables to explain changes in attitude and behavior, related to MRI uses. Practical implications: Overall, corporations should use MRI more thoroughly. Treating the MRF as a strategic asset rather than just another internal service provider increases its value to the firm. Firms should thus bolster the MRF's different roles, namely, internal colleague, service provider, customer representative, quality assurance, and knowledge broker. Originality/value: This paper is the first to comprehensively analyze the MRF's role in MRI generation and various uses. It identifies three expertise dimensions of the MRF to fully leverage the MRF's value to the organization and empirically underscores theoretical writings on the MRF's roles in the firm.